Development of JT-60SA equilibrium controller with an advanced ISO-FLUX control scheme in the presence of large eddy currents and voltage saturation of power supplies. (27th July 2021) - Inoue, S.; Miyata, Y.; Urano, H.; Suzuki, T.
Abstract: An advanced ISO-FLUX equilibrium control scheme is developed and implemented in the JT-60SA equilibrium controller. For future fusion reactor, the VDE control by the active superconducting coils is essential due to the absence of in-vessel coils and stabilization plates, and the presence of large gap between plasmas and vacuum vessels with the tritium breeding blanket. Under the circumstances, the equilibrium controller should achieve plasma position/shape control and plasma current control by superconducting coils within limited power supply voltages, where plasma current control affects plasma position/shape control, and vice versa. The newly developed ISO-FLUX control scheme enhances the controllability under the above hybrid control of position/shape and plasma current circumstances. Furthermore, the new scheme also provides good controllability under large eddy currents conditions, which will also be expected in future superconducting tokamaks, such as JT-60SA, ITER, and DEMO due to its large inductance and high target plasma current. The JT-60SA equilibrium controller with the developed scheme is well verified by a magnetohydrodynamic equilibrium control simulator 'MECS' and ready for the integrated commissioning of JT-60SA.